Who leaves, where to, and why worry? employee mobility, entrepreneurship and effects on source firm performance - Campbell, Benjamin A.; Ganco, Martin; Franco, April M.; Agarwal, Rajshree (Strategic Management Journal, 2012)
Abstract We theorize that the value provided by the firm's complementary assets has important implications for the exit decisions of employees and their subsequent effects on the firm's performance. Using linked employee‐employer data from the U.S. Census Bureau on legal services, we find that employees with higher earnings are less likely to leave relative to employees with lower earnings, but if they do, are more likely to create a new venture than join another firm. Employee entrepreneurship has a larger adverse impact on source firm performance than moves to established firms, even controlling for observable employee quality. Our findings suggest that in knowledge intensive settings, managers should focus on tailoring compensation packages to help minimize the adverse impact of employee entrepreneurship, particularly among high performing individuals. Copyright © 2011 John Wiley & Sons, Ltd.